Batch Sorption of Copper (II) Ions from Simulated Aqueous Solution by Banana Peel - Faisal M., Lahieb Faisal M. (Al-Khwarizmi Engineering Journal, 2017)
This research presents the possibility of using banana peel (arising from agricultural production waste) as biosorbent for removal of copper from simulated aqueous solution. Batch sorption experiments were performed as a function of pH, sorbent dose, and contact time. The optimal pH value of Copper (II) removal by banana peel was 6. The amount of sorbed metal ions was calculated as 52.632 mg/g. Sorption kinetic data were tested using pseudo-first order, and pseudo-second order models. Kinetic studies showed that the sorption followed a pseudo second order reaction due to the high correlation coefficient and the agreement between the experimental and calculated values of qe. Thermodynamic parameters such as enthalpy change (ΔH°), entropy change (ΔS°) and Gibbs free energy change (ΔG°) were also investigated. Free energy change showed that biosorption of Cu (II) was spontaneous and nature endothermic at all studied temperatures (25–45 °C).